Does Going Public Affect Innovation? - BERNSTEIN, SHAI (Journal of Finance, 2015)
ABSTRACT This paper investigates the effects of going public on innovation by comparing the innovation activity of firms that go public with firms that withdraw their initial public offering (IPO) filing and remain private. NASDAQ fluctuations during the book‐building phase are used as an instrument for IPO completion. Using patent‐based metrics, I find that the quality of internal innovation declines following the IPO, and firms experience both an exodus of skilled inventors and a decline in the productivity of the remaining inventors. However, public firms attract new human capital and acquire external innovation. The analysis reveals that going public changes firms' strategies in pursuing innovation.